Akuntabilitas dan Transparansi Pengelolaan Badan Usaha Milik Desa “Jaya Tirta” - Nanda Ayu Ariski; Muhammad Asim Asy'ari (Program Studi Akuntansi Fakultas Ekonomi dan Bisnis Universitas Mahasaraswati Denpasar, 2022)
Village-Owned Enterprises are business entities formed and established by the village with the aim of managing the potential of the village in order to strengthen the village economy. As a new entity, it is important for BUMDes to pay attention to aspects of good governance, especially accountability and transparency, which are the main keys in business management in order to avoid misuse of funds that can result in the BUMDes business stalling. This study was conducted with the aim of analyzing the extent to which the principles of accountability (process and output) and transparency are applied in the management of BUMDes Jaya Tirta, Kanor District, Bojonegoro Regency. This research is a case study qualitative research. The types of data used are primary and secondary data. Data collection techniques were carried out through observation, interviews, and documentation by going directly to the research site. The data analysis technique in this study was carried out with a disciplined comparative. The results show that the financial management of BUMDes Jaya Tirta has been carried out in an accountable and transparent manner by BUMDes managers so that it has an impact on the progress and success of BUMDes.